PERSEPSI ORANG TUA TERHADAP PELAKSANAAN PEMBELAJARAN TATAP MUKA DI TK ABA 2 SUMBERSARI JEMBER - Ismanto, Suci Maulidiah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2024)
In June 2020 the government has planned a new era during this pandemic, namely the new normal era. In the world of education, limited face-to-face learning plans (PTMT) during the new normal era, received very diverse responses from parents or guardians of students. Some give a positive response but some offer the opposite response. With various reasons that support each response given. One of the cases of early childhood (AUD) exposure to COVID-19 is increasing day by day, making parents hesitate to permit their children to carry out face-to-face learning, especially at the PAUD level. However, in some conditions, parents feel that learning from home is less effective. This study wants to describe how parents perceive PTMT implementation in TK ABA 2 Sumbersari Jember. This research uses descriptive quantitative research with a survey approach. The research subjects are parents (guardians of students) in Group B. The data collection methods used are observation, questionnaires, and documentation. The data analysis technique used is crosstabulation. The results of the research showed that 50% answered agree, 38% answered strongly agree, 11% answered in doubt and 1% answered disagree on the questionnaire that was distributed, which means that most parents accept and apply all the rules made by the school during the Covid 19 period, so that PTMT can be carried out 3 times a week at ABA 2 Sumbersari Jember Kindergarten in the odd semester of the 2021/2022 school year.